Translating XML-Based Documents Using XML technology to reduce the cost of authoring and translation. - Zydron, Andrzej
Xml : tm is an XML namespace-based technology designed to substantially reduce the costs of translating XML documents while at the same time providing the architecture to build consistent authoring systems. xml: tm is an open standard maintained by XML-Intl for the benefit of those involved in the translation of XML documents.